Thalamic nuclei volumes are related to disease stage in patients with amyotrophic lateral sclerosis - Tianrui Wen; Tianrui Wen; Jun Zhu; Jun Zhu; Sujuan Sun; Sujuan Sun; Yujing Chen; Yujing Chen; Ninglu Gao; Ninglu Gao; Mingjie Ma; Xinyue Chen; et al. (Frontiers in Neuroscience)
ObjectiveTo explore atrophy patterns in thalamic nuclei at different phases of amyotrophic lateral sclerosis (ALS) and determine any correlations between thalamic nucleus volume and either cognitive impairments or motor disabilities.MethodsWe used the King’s clinical staging system for ALS to divide 76 consecutive patients with ALS by disease stage. We investigated patterns of thalamic atrophy in the patients and in 94 healthy controls (HCs). Cognitive functions were evaluated with the Mini-Mental State Examination (MMSE), Frontal Assessment Battery, Boston Naming Test, and Auditory Verbal Learning Test.ResultsConsidering all ALS patients, no significant differences were observed in the volume of any thalamic nuclei between the ALS group and HCs. Thalamic nucleus volumes remained normal in ALS patients at King’s Stage 2 and Stage 3. However, atrophy was detected in the bilateral anteroventral nucleus, bilateral pulvinar-limitans, bilateral mediodorsal-paratenial-reuniens, bilateral motor hub, bilateral sensory hub, and bilateral intralaminar nucleus in patients who had reached King’s Stage 3. In these patients, the volume of the bilateral motor nuclei was associated with the revised ALS Functional Rating Scale scores, and that of the right pulvinar-limitans independently correlated with MMSE scores.ConclusionOur study provides a comprehensive profile of thalamic atrophy in ALS patients. The thalamic atrophy patterns in these patients extremely differs at different King’s Stages, and we suggest that these alterations might result largely from sequential, regional patterns of TDP-43 pathology in ALS. Furthermore, thalamic atrophy might play important roles in motor disability and global cognitive impairments observed in patients with ALS.